An unusual cross reactivity between hydrochlorothiazide and para-phenylenediamine: a case report - Patil, Deena; Sumathy, Tharayil K.; Anuradha, Hassan V. (International Journal of Research in Medical Sciences, 2022)
Over the last decade, the usage of hair color is gradually increasing from adolescents to the geriatric population. In the elderly population, more use of hair color due to graying of hairs exposes them to chemicals such as para-phenylenediamine (PPD). Many cases are reported regarding various manifestations of allergic contact dermatitis due to PPD compound present in hair color. It is noteworthy that, in the elderly the use of antidiabetics and antihypertensives, makes them vulnerable to cross-reaction or interaction with drugs and chemicals. We report a case that highlights the adverse reaction to hydrochlorothiazide in a PPD sensitive individual.